The Effects of Traditional Kurdistan Plant Extracts on Rat Hair Growth in vivo - Mahmood, Kochar I; Khidhir, Karzan G. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Pathologies of hair growth can be psychologically distressing but they are poorly controlled. Hormones and paracrine factors regulate the hair follicle and its associated glands. However, our understanding of their mechanisms is limited, restricting the development of new treatments for hair disorders. Therefore better treatments for hair loss disorders are required. Some plant extracts are believed to have effect on hair growth. Few local plants in Kurdistan region are used traditionally as stimulators of human hair growth, but their effects on hair growth scientifically has not been studied yet. Therefore, the aim of this study was to investigate the actual effects of those local plant extracts used as a traditional herbal treatment for hair loss, using in vivo rat model (Wistar-Bratislava rats); and to compare their effectiveness with the best medical treatment available (Minoxidil). The effects of extracts from Myrtus (Myrtus communis), Galls (Quercus infectoria), Oak (Quercus aegilops) both separately and mixed at the recommended concentrations were compared with the medical treatment for hair loss and a negative control group. Shaved backs of Wistar rats (6 weeks old) were treated daily for 42 days (six groups, n=6 per group), and the degree of their effectiveness was observed and compared with each other and with both positive and negative controls. Results show that the mixture of the three plants extracts and Minoxidil have similar significant hair growth promotion effect compared to other groups. Therefore, extracts from Myrtus, Galls and Oak stimulate rodent pelage follicles in vivo suggesting they can be used as promoter of hair growth in human.
Keywords: Hair growth; in vivo study; plant extracts; Wistar rats